Protection against STDs: an Islamic criminal law approach - Deuraseh, Nurdeng @ Nurdeen (Brill, 2008)
In Islamic law, there is a principle known as sadd al-dharā'i, or blocking the means. By virtue of blocking the means, any particular action, which may bring harm to mankind, would be deemed unlawful and illegitimate. To apply this concept, Islam does not tolerate the practice of unlawful sexual relations. It is found that many victims of STDs and HIV/AIDS are those who practice sodomy or even anyone who maintains sexual relations with anyone other than his/her lawful spouse. In Islam, al-zinā (tr. adultery and fornication) and al-liwāt (tr. homosexuality) are crimes not only against one person but against society as a whole. The present paper will study the role of Islamic criminal law in the prevention of Sexually Transmitted Diseases (STDs) in general, and HIV/AIDS in particular.